Larvicidal Activity of Essential Oils From Piper Species Against Strains of Aedes aegypti (Diptera: Culicidae) Resistant to Pyrethroids - Pereira Filho, Adalberto Alves; Pessoa, Grasielle C. D‘Ávila; Yamaguchi, Lydia F.; Stanton, Mariana Alves; Serravite, Artur M.; Pereira, Rafael H. M.; Neves, Welber S.; Kato, Massuo Jorge (Frontiers in Plant Science, 2021)
The continuous and indiscriminate use of insecticides has been responsible for the emergence of insecticide resistant vector insect populations, especially in Aedes aegypti. Thus, it is urgent to find natural insecticide compounds with novel mode of action for vector control. The goal of this study was to investigate the larvicidal activity of essential oils (EOs) from Piper species against A. aegypti characterized as resistant and susceptible strains to pyrethroids. The EOs from leaves of 10 Piper species obtained by hydrodistillation were submitted to the evaluation of larvicidal activity in populations of A. aegypti in agreement with the WHO (2005) guidelines. The resistance of the strains characterized by determining the lethal concentrations (LCs) with the insecticide deltamethrin (positive control). The major compounds of the EOs from Piper species was identified by GC-MS. The EOs from Piper aduncum, P. marginatum, P. gaudichaudianum, P. crassinervium, and P. arboreum showed activity of up to 90% lethality at 100 ppm (concentration for screening). The activities of the EOs from these 6 species showed similar LCs in both susceptible strain (Rockfeller) and resistant strains (Pampulha and Venda Nova) to pyrethroids. The major compounds identified in the most active EO were available commercially and included β-Asarone, (E)-Anethole, (E)-β-Caryophyllene, γ-Terpinene, p-Cymene, Limonene, α-Pinene and β-Pinene. Dillapiole was purified by from EO of P. aduncum. The phenylpropanoids (Dillapiole, (E)-Anethole and β-Asarone) and monoterpenes (γ-Terpinene, p-Cymene, Limonene, α-Pinene, and β-Pinene) showed larvicidal activity with mortality between 90 - 100% and could account for the toxicity of these EOs, but the sesquiterpene (E)-β-Caryophyllene, an abundant component in the EOs of P. hemmendorffii and P. crassinervium, did not show activity on the three populations of A. aegypti larvae at a concentration of 100 ppm. These results indicate that Piper's EOs should be further evaluated as a potential larvicide, against strains resistant to currently used pesticides, and the identification of phenylpropanoids and monoterpenes as the active compounds open the possibility to study their mechanism of action.